GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 729696 species occurrences available in GBIF matching the query: TaxonKey: Arecaceae HasCoordinate: true HasGeospatialIssue: false. The dataset includes 729696 records from 499 constituent datasets: 1 records from Bioimages. 2 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 3 records from Inventory of Wari maro forest (Benin). 3 records from National Biodiversity Data Bank. Observation records, 1900-2014. 63 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 18 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 7 records from JOI - Herbário Joinvillea. 7981 records from OEH Atlas of NSW Wildlife. 1464 records from A global database for the distributions of crop wild relatives. 1 records from Tejidos colectados en la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 6 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 117 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 9 records from HUEM - Herbário da Universidade Estadual de Maringá. 2 records from HUFU - Herbarium Uberlandense. 159 records from Phanerogamic Botanical Collections (S). 100 records from PRECIS (KwaZulu-Natal Herbarium). 62 records from University of Vienna, Institute for Botany - Herbarium WU. 554 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 43 records from UFG - Herbário da Universidade Federal de Goiás. 97 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 213 records from Colección nacional de palmas de Colombia - JBQ. 53 records from Census of the flora of Benin. 2 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 235 records from IAC - Herbário do Instituto Agronômico de Campinas. 70 records from Agroforestry plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 65 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 4 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 3 records from Census of secondary forest of Itchèdè-Toffo (Southern Benin). 14 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 5230 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 32 records from SPSF - Herbário Dom Bento José Pickel. 385 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 86 records from PRECIS. 8539 records from Herbario Nacional Colombiano (COL). 8 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 4 records from Flora del municipio de Culiacán, Sinaloa. 1 records from UTEP Plants (Arctos). 128 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 11 records from Computarización de las colectas del estado de Morelos depositadas en el Herbario HUMO de la Universidad Autónoma del Estado de Morelos. 527 records from SPF - Herbário da Universidade de São Paulo. 20 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 6 records from Fauna y flora de la cuenca media del río Lebrija en Rionegro, Santander. 20 records from Census of plant species in Bonou forest reserve (Southern Benin). 46 records from UFP - Herbário UFP - Geraldo Mariz. 2 records from Registros restauración ecológica- Magdalena medio. 1 records from NPL collections. 130 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 2 records from Tejidos colectados en la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 1870 records from Colección Herbario Federico Medem Bogotá - FMB. 2 records from Checklist of aquatic and marshy Monocotyledons from the Araguaia River basin, Brazilian Cerrado. 1 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 65 records from HERBAM - Herbário da Amazônia Meridional. 120 records from Herbario Pontificia Universidad Javeriana. 14 records from ICN - Herbário do Instituto de Ciências Naturais. 29 records from IICT Herbário LISC. 254 records from Herbario Universidad de Antioquia (HUA). 51 records from Inventario Español de Especies Terrestres (MAGRAMA). 2 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 253 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 17 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 45 records from Árboles de Chiapas: registro georreferenciado de los ejemplares depositados en el herbario de la Academia de Ciencias de California (CAS). 5 records from BioGIS - Vascular plants - Israeli Gene Bank. 85 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 9 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 3 records from Fauna y flora del municipio de Tame, Arauca. 236 records from The digitization of plant specimens of NTU. 3 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 307 records from SA Flora (BDBSA). 12 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 787 records from Depuración de la colección y base de datos del Herbario CICY. Fase IV. 345 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 27 records from Colección Herbario Universidad Católica de Oriente. 8 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 28 records from Museu Paraense Emilio Goeldi Herbarium. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 79 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 42 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 1 records from CESJ - Herbário Leopoldo Krieger. 1 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 162 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 14 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 3 records from Plantas alimenticias incluidas en la dieta local en el municipio de Montería, Córdoba. 1 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 42 records from HAMAB - Herbário Amapaense. 4 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 1 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 4357 records from Plantae of Costa Rica (INBio). 2 records from Bases de datos del proyecto análisis de la riqueza y el endemismo de la flora de México, con fines de su conservación, usando grupos y métodos selectos. 4 records from MATRIX project, Mabira in Uganda. 157 records from Artdata. 17 records from Herbier du Bénin. 5 records from Flora of tanzania. 3 records from Two new records of palm species for Gabon: Sclerosperma profizianum Valk. & Sunder. and Eremospatha quiquecostulata Becc.. 34 records from MBM - Herbário do Museu Botânico Municipal. 87 records from Flora de las playas y dunas costeras de México. 3 records from Estudio de la diversidad florística de la región de Nizanda en el Istmo de Tehuantepec, Oaxaca. 2 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase I (Tenango de Doria y Tlanchinol). 1271 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 7 records from Lista florística de la Costa Grande del estado de Guerrero. 102 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 2 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 25 records from Endemic plants of the Congo basin. 691 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 2 records from Données ONF Faune-Flore-Fonge. 282 records from Herbier de Nouvelle-Calédonie. 28 records from Herbarium areqvipense (HUSA). 85 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 93 records from La familia Asteraceae en México. Fase VI. 28 records from Herbarium of the Université Libre de Bruxelles. 8501 records from Australia's Virtual Herbarium. 1221 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 256 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 2 records from Plantas Bosque Seco Chicamocha. 445 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 127 records from Dados de ocorrência de espécies da flora da Guiné-Bissau. 7 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 30 records from Kathryn Kalmbach Herbarium. 2 records from Natural History Museum Maastricht (NL) - Herbarium. 198 records from Consortium of California Herbaria. 2 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 1337 records from iNaturalist Research-grade Observations. 56 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 1 records from UCBG TAPIR Provider. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 60 records from CONN. 39 records from HUCS - Herbário da Universidade de Caxias do Sul. 51 records from Registros biológicos de especies de plantas del Bosque Seco en Colombia presentes en el Herbario JBGP. 19 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 96 records from Base de datos del Herbario CIQR de El Colegio de la Frontera Sur, unidad Chetumal. 61 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 204 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forèts sacrées des départements de l'Ouémé-Plateau et le Collines. Données mobilisées dans le cadre du projet JRS Bénin. 84 records from Composición florística y estructura de una parcela permanente en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 43 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 1 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 2 records from Herbier National de Mauritanie (HNM). 4 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 41 records from BioGIS - Vascular plants - INPA database. 2 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 175 records from Las monocotiledóneas mexicanas, una sinopsis florística. 305 records from ALCB - Herbário Alexandre Leal Costa. 33 records from Caracterización biológica del Monumento Natural Yaxchilán como un elemento fundamental para el diseño de su plan rector de manejo. 2 records from corrego_fazendinha-gallery-forest_v2. 1 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 3 records from BioGIS - Vascular plants - A. Danin's point database. 6 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 7 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 17 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 24 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos). 24 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 4 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv).. 9 records from Caracterización biológica de la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia. 18 records from Census of plant species in Toffo forest reserve. 670 records from naturgucker. 4 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 2 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 24 records from Census in Agrimey forest reserve (southern Benin). 89 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 11 records from Colección de Plantas Vasculares del Herbario Forestal UDBC "Gilberto Emilio Mahecha Vega". 77 records from MfN - Fossil plants (Cenophytic). 3 records from MfN - Fossil plants (Mesophytic). 17 records from MfN - Fossil plants (Paleophytic). 5 records from Community dynamics in a species-rich patch in the Brazilian Atlantic Forest near Viçosa/MG. 6 records from Caracterización florística de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 40 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del piedemonte de Arauca, municipio de Tame. 6039 records from Flora Atlas N.T.. 1253 records from INPN - Données flore des CBN agrégées par la FCBN. 48 records from Herbier de Wallis et Futuna. 8 records from EFC - Herbário Escola de Florestas Curitiba. 147 records from ASE - Herbário da Universidade Federal de Sergipe. 53 records from UEC - Herbário da Universidade Estadual de Campinas. 2617 records from NZ National Vegetation Survey occurrence data. 2 records from BioBlitz Barcelona 2010-14. 16 records from FUEL - Herbário da Universidade Estadual de Londrina. 1095 records from ICN - Universidad Nacional de Colombia. 1992 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 5 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 826 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 132 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 157 records from Colección de Monocotiledóneas Mexicanas (UAM-I). 13 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 12 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 21 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 13 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 24 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 1 records from Tiroler Landesmuseum Ferdinandeum. 2 records from The Fungal Collection at the Botanische Staatssammlung München. 1 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 51 records from Inventario florístico de los cerros San Martí y El Patol en el semidesierto queretano. 23083 records from Tropicos Specimen Data. 21 records from BRERC species records recorded over 15 years ago. 45 records from Caracterización del hábitat de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 570 records from Natural History Museum (London) Collection Specimens. 4 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 43 records from Natural History Museum, Vienna - Herbarium W. 10 records from Flora útil del Municipio de la Huerta, Jalisco. 4 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 4 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 78 records from Flora acuática vascular del área focal Felipe Carrillo Puerto, Corredor Biológico Sian Ka'an-Calakmul, Quintana Roo, México. 21 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 18 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 14 records from Diversidad florística y endemismo en la Reserva de la Biósfera El Cielo, Tamaulipas, México. 6 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase II (Tlahuelompa y Eloxochitlán). 146 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 48 records from Lista florística preliminar de Tamaulipas. 10 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 17 records from Inventario de la vegetación acuática vascular de la reserva de la biosfera Pantanos de Centla, Tabasco. 3 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 836 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 2 records from Florística de la reserva de la biósfera de Mapimí. 32 records from Contribución al conocimiento de la flora útil de la selva Lacandona. 2 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 1 records from Computarización del Herbario ENCB, IPN. Fase IV. Base de datos de la familia Pinaceae y de distintas familias de la clase Magnoliopsida depositadas en el Herbario de la Escuela Nacional de Ciencias Biológicas, IPN. 64 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 2 records from Base de datos del Herbario de la Unidad Académica de Agronomía de la Universidad Autónoma de Zacatecas. 172 records from Flora-On: occurrence data of the flora of mainland Portugal. 758 records from Investigaciones sobre recursos no maderables de México: biología evolutiva y conservación de plantas del género Chamaedorea. 14 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 2 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 19 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 8 records from Flora de las Barrancas del Cobre. 261 records from Inventario nacional de especies vegetales y animales de uso artesanal. 2 records from Potencial económico de la flora útil de los cafetales de la Sierra Norte de Puebla. 30 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 134 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 62 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 9 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 72 records from Formación del banco de datos del herbario (UCAM). 78 records from Computarización de la colección de plantas acuáticas mexicanas del Herbario Nacional (MEXU). 55 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 54 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 2 records from Base de datos sobre la flora de Durango. 40 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 2 records from Inventario florístico de la Sierra de Huautla, Morelos. 103 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 70 records from Estudio de la diversidad florística en la región de la Chinantla, Sierra Norte de Oaxaca. 12 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 28 records from West African Vegetation Database. 22 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 78 records from Flora acuática vascular y de zonas inundables del área de protección de flora y fauna Laguna de Términos, Campeche, México. 10 records from Base de datos para la xiloteca del Instituto de Biología de la UNAM. 4 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 1 records from Tartu University, palaeontology collections. 1 records from Inventory of Penessoulou forest (North West Benin). 1145 records from NMNH Extant Specimen and Observation Records. 1 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 6 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 1 records from Mountain Invasion Research Network (MIREN) survey. 67 records from Andes to Amazon Biodiversity Program. 317 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 3289 records from The AAU Herbarium Database. 12 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 1 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 123 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 4 records from Herbario de la Universidad de Almeria. 2 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 17 records from Jardín Botánico de Córdoba: Herbarium COA. 1 records from Aranzadi Zientzi Elkartea. 6 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 1 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 101 records from Herbario de la Universidad de Sevilla. 21 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 8 records from Institut Botanic de Barcelona, BC. 2 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 342 records from Auckland Museum Botany Collection. 6 records from AIMS - Bioresources Library (OBIS Australia). 160 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé et du Plateau. Data mobilized in the framework of JRS Biodiversity Foundation project. 351 records from Paleobiology Database. 1577 records from herbario. 8 records from Plant Specimens of Kurashiki Museum of Natural History. 1 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 2 records from Individual Sightings. 42 records from DAV UC Davis Center for Plant Diversity. 44 records from Herbarium (UNA). 17 records from MEXU/Plantas Vasculares. 1 records from MEXU/Tipos de plantas vasculares. 1248 records from Actualización de las bases de datos del Herbario XAL. Fase III. 893 records from Plants of Papua New Guinea. 37 records from Herbarium Berolinense. 5 records from Observations du Conservatoire botanique national du Bassin parisien.. 91 records from Biologiezentrum Linz. 1 records from United States National Plant Germplasm System Collection. 148 records from Israel Nature and Parks Authority. 16 records from Herbarium de Geo. B. Hinton, México. 26 records from Harvard University Herbaria. 3 records from Vascular plants of south-central China. 21 records from BioGIS - Vascular plants - A. Danin's grid database. 2 records from EURISCO, The European Genetic Resources Search Catalogue. 4 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 16 records from CVRD - Herbário da Reserva Natural Vale. 15 records from Kochi Prefectural Makino Botanical Garden. 15 records from MAR - Herbário do Maranhão. 18339 records from Primer censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 44 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Chingaza. 10 records from Herbario de la Universidad de Arizona, EUA. 4 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 186 records from Árboles de la Península de Yucatán, Flora del Distrito de Tehuantepec, Oaxaca y Familia Asteraceae en México (IBUNAM). 1 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 8 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 113 records from USF Herbarium. 38 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 5 records from Caracterización biológica de la ventana de biodiversidad Ciénaga, Municipio de Ciénaga, Magdalena, Colombia. 7 records from HPAN - Herbário do Pantanal "Vali Joana Pott". 3 records from Herbier Ecole de Faune. 4 records from Atlas Flora Danica. 79 records from Census of the threatened species of Benin.. 2 records from Lichens of North-Eastern Poland. 1 records from Computarización del Herbario ENCB. Fase II. Base de datos de los ejemplares de la familia Burseraceae y Nyctaginaceae y base de datos digitalizada de los ejemplares tipo de plantas vasculares del Herbario de la Escuela Nacional de Ciencias Biológicas. 2 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 1706 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1552 records from MBML-Herbario - Herbário Mello Leitão. 1 records from Espèces vasculaires endémiques et orchidées (CITES). 14 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 2 records from R. L. McGregor Herbarium Vascular Plants Collection. 3102 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 3 records from Colección de plantas vasculares de Brasil del Herbario "Jaime Andrés Rodríguez". LEB-Brasil. 108 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 112 records from MEXU/Colección de Plantas Acuáticas. 1 records from Jardín Botánico Atlántico, Gijón: JBAG. 47 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 10 records from Biological and palaeontological collection and observation data MNHNL. 1 records from Flora de los ecosistemas de la zona alta del río Coello (Tolima, Colombia). 1 records from Botany Division, Yale Peabody Museum. 134 records from Paleobotany Division, Yale Peabody Museum. 6 records from HUTO - Herbário da Universidade de Tocantins. 21 records from Herbarium Senckenbergianum (FR). 22 records from NHT_flora. 11 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 24 records from MEXU/Flora de Oaxaca. 4 records from Herbario de Universidad de Murcia: MUB. 32 records from Database of Native Plants in Taiwan. 102 records from University of Ghana - Ghana Herbarium. 34 records from Herbarium of Taiwan Forestry Research Institute. 156 records from Etapa final de la captura y catalogación del Herbario del Instituto de Ecología, AC, Centro Regional del Bajío. 197 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Pereira, Risaralda. 2 records from Plant inventory of W Biosphere reserve (North-Benin). Data mobilized in the framework of JRS Biodiversity Foundation project. 3092 records from Herbario Amazónico Colombiano. 220 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 3 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 105 records from Banco de datos florísticos del Herbario CHAP. 13 records from WII Herbarium Dataset. 792 records from National vegetation diversity inventory and mapping plan. 1 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 3 records from La vegetación y flora de las Lagunas de Catazajá-Emiliano Zapata. 59 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 447 records from Integración de bases de datos, actualización y sistematización de la colección de flora del Herbario Eizi Matuda (HEM). 14 records from Jardín Botánico Uniamazonia JBUA. 646 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 69 records from UPCB - Herbário do Departamento de Botânica. 1 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 65 records from Bosque Mesófilo de Montaña de México. 5 records from Tejidos colectados en la ventana de biodiversidad Ciénaga, Municipio de Ciénaga, Magdalena, Colombia. 3 records from Heritage Trees of Ireland. 22 records from HURB - Herbário do Recôncavo da Bahia. 540958 records from Aarhus University Palm Transect Database. 12 records from Elaboration du tarif de cubage multispécifique. 11 records from Lund Botanical Museum (LD). 59 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 24 records from Herbario CTES Plantas Vasculares. 3 records from Plantas vasculares de la Sierra Tarahumara -listado florístico, etnobotánico e histórico-. 45 records from Census of medicinal plants of Benin.. 3 records from HVAT - Herbário do Vale do Taquari. 195 records from Geographically tagged INSDC sequences. 1 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 10 records from TEPB - Herbário Graziela Barroso. 5 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 158 records from HTSA - Herbário do Trópico Semiárido. 49 records from HVASF - Herbário Vale do São Francisco. 35 records from Plantas laguna El Tinije. 180 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from HST - Herbário Sérgio Tavares. 309 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 9 records from R-Tipos - Herbário do Museu Nacional - Tipos. 2748 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from Herbier_CNSF. 27 records from SBT-Living. 289 records from Bernice P. Bishop Museum. 11 records from Fauna y flora del municipio de Lipa, Arauca. 165 records from FURB - Herbário Dr. Roberto Miguel Klein. 69 records from Cuarenta y ocho especies de la flora de Chiapas incluidas en el PROY-NOM-059-ECOL-2000. 103 records from Carnet en Ligne. 34 records from CRI - Herbário Pe. Dr. Raulino Reitz. 2 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 542 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 17 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 5 records from Condon Fossil Collection. 32 records from Actualización de la base de datos sobre la flora de la Reserva de la Biósfera Sierra de Manantlán, Jalisco-Colima, México. 91 records from Royal Botanic Garden Edinburgh Herbarium (E). 18 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 12 records from Botany (UPS). 2919 records from Instituto de Ciencias Naturales. 5 records from La flora útil de dos comunidades indígenas del Valle de Tehuacán-Cuicatlán: Coxcatlán y Zapotitlán de las Salinas, Puebla. 11 records from CNMT - Herbário Centro Norte Mato Grossense. 5 records from HAS - Herbário Alarich Rudolf Holger Schultz. 41 records from Inventario Florístico de la Reserva de la Biósfera La Sepultura del Corredor Biológico Sierra Madre del Sur. Fase II. 2 records from University of British Columbia Botanical Garden Collections (UBCBG). 10 records from Conservación del germoplasma vegetal en las regiones áridas y semiáridas de México. Fase 5. 16 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 118 records from Census of species recorded during phytosociological surveys in Benin. 84 records from UFPB - Herbário Lauro Pires Xavier - (JPB). 16 records from EAC - Herbário Prisco Bezerra. 311 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 16 records from Herbario de la Universidad Industrial de Santander. 61 records from Base de datos computarizada del herbario CIB, Instituto de Investigaciones Biológicas, Universidad Veracruzana. 7254 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 36 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 25 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 32 records from Ecology, structure and dynamics of private plantations of Teck (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 2 records from Registros de flora de las caracterizaciones rápidas de coberturas en los municipios de Beltrán y Guataquí, Cundinamarca. 28 records from Ecological inventory of Borassus aethiopum (Mart.) populations in the Pendjari Biosphere Reserve, Benin. Data mobilized in the framework of JRS Benin project. 17 records from Incremento de los bancos florístico y etnobotánico de la Península de Yucatán. 15 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 69 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 4 records from Vascular plant herbarium, NTNU University Museum. 2 records from Données ONF Faune-Flore-FOnge. 15 records from Dados da ocorrência de plantas lenhosas em um gradiente de perturbação/precipitação em área de Caatinga, Parque Nacional do Catimbau, Buíque, PE, Brasil. 64 records from New Zealand Biodiversity Recording Network. 4794 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 1464 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 1 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 8 records from Caracterización biológica de la ventana de biodiversidad municipio de Filandia, Quindío, Colombia. 5 records from Caracterización biológica de la ventana de biodiversidad enclave Atuncela, municipio de Dagua, Valle del Cauca. 5 records from Wilson Botanical Garden - Las Cruces Biological Station. 14 records from SLUI - Herbário Rosa Mochel. 4 records from Phanérogames recensés aux Monts Nimba. 368 records from UB - Herbário da Universidade de Brasília. 1 records from Université Pédagogique Nationale de Kinshasa (UPN) - Données botaniques (2011)- Projet CABIN. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 96 records from Regeneración de especies arbóreas del bosque mesófilo en las montañas del norte de Chiapas. 24 records from Herbarium - Las Cruces Biological Station. 2 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 18339 records from Segundo censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 74 records from Actualización e incremento de la base de datos del Herbario de la Benemérita Universidad Autónoma de Puebla. 83 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 3 records from Herbier CNRST/INERA. 251 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales de afloramiento rocoso del Parque Nacional Natural El Tuparro. 13 records from Herbier National de Guinée (HNG). 27 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 5 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 21 records from Allan Herbarium (CHR). 9 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 12 records from Caracterización biológica de la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 182 records from HPL - Herbário do Jardim Botânico Plantarum. 1 records from Auckland Museum NZ Marine Collection. 43 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 488 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 7 records from Vascular Plant Herbarium, Oslo (O). 628 records from Occurrences in SinBIOTA. 138 records from African Plants - a photo guide. 1 records from Anymals+plants - Citizen Science Data. 4 records from Flora von Deutschland (Phanerogamen). 2 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 98 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 28 records from Propuesta para sistematizar la colección palinológica de polen reciente y fósil del IGLUNAM. 127 records from Sistematización del Herbario Nacional Forestal Biól Luciano Vela Gálvez. 8 records from HDJF - Herbário Dendrológico Jeanine Felfili. 18 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 10 records from Census of plant species in Monts-Kouffè regions, center Benin. 66 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 1 records from Caracterización de coberturas vegetales en el páramo de Santurbán. 1 records from Auckland Museum Marine Collection. 4 records from Fusión y actualización de las bases de datos del Herbario de la Facultad de Ciencias, UNAM (FCME), Guerrero. 37 records from Levantamento do estrato arbustivo da vegetação de campina do RDS Uatumã. 188 records from Distribution de quelques espèces de plantes agroforestières et médicinales au Bénin. 315 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 70 records from Census of plant species in Pahou forest reserve. 2 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3 records from Tejidos colectados en la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia.. 1 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 2443 records from The census of national forest of Benin .. 2 records from Diversidad florística y estado de conservación en dos ventanas de paisaje de la UPR Tunjuelo priorizadas: Usme y Ciudad Bolivar, Bogotá. 84 records from SysTax - Herbaria. 88 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 5 records from Abundancia, distribución y estado de conservación de Guaiacum sanctum L. en México. 548 records from Geneva Herbarium – General Collection (G). 201 records from Instituto de Botánica Darwinion. 1 records from Flora vascular de los manglares de Marismas Nacionales, estado de Nayarit. 6 records from JOIw - Xiloteca Joinvillea. 110 records from Estudio demográfico y genético de Desmoncus quasillarius Bartlett (Arecaceae). 1 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 10 records from Herbario Virtual Bosques Secos de Colombia - Sección Herbario Universidad de Córdoba (HUC). 71 records from UFMT - Herbário UFMT. 81 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 135 records from CAS Botany (BOT). 53 records from CPAP - Herbário CPAP. 98 records from Computarización de la base de datos del Banco Nacional de Germoplasma Vegetal - Fase 2. 405 records from Tercer Inventario Forestal Nacional. Ministerio de Agricultura, Alimentación y Medio Ambiente (España/Spain). 9 records from Dieta y preferencias alimenticias de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 66 records from HEPH - Herbário Ezechias Paulo Heringer. 2676 records from Establecimiento de línea base para el monitoreo de especies de plantas de interés para la conservación. 6 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 1 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 1 records from Forest inventory for above ground carbon estimation in Biosphere Reserve of W. Data mobilized in the framework of the BID-AF2015-0030-SMA project of Isidore AMAHOWE. 13 records from MOSS - Herbário Dárdano de Andrade Lima. 32 records from HRCB - Herbário Rioclarense. 2 records from PACA-AGP - Herbarium Anchieta. 1 records from Millenium Seedbank (MSB). 56 records from UESC - Herbário Universidade Estadual de Santa Cruz. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences